Ultraviolet and photosynthetically active radiation can both induce photoprotective capacity allowing barley to overcome high radiation stress - Klem, Karel; Holub, Petr; Štroch, Michal; Nezval, Jakub; Špunda, Vladimír; Tříska, Jan; Jansen, Marcel A K; Robson, T Matthew; Urban, Otmar (Plant physiology and biochemistry, 2015)
The main objective of this study was to determine the effects of acclimation to ultraviolet (UV) and photosynthetically active radiation (PAR) on photoprotective mechanisms in barley leaves. Barley plants were acclimated for 7 days under three combinations of high or low UV and PAR treatments ([UV-PAR-], [UV-PAR+], [UV+PAR+]). Subsequently, plants were exposed to short-term high radiation stress (HRS; defined by high intensities of PAR - 1000 μmol m(-2) s(-1), UV-A - 10 W m(-2) and UV-B 2 W m(-2) for 4 h), to test their photoprotective capacity. The barley variety sensitive to photooxidative stress (Barke) had low constitutive flavonoid content compared to the resistant variety (Bonus) under low UV and PAR intensities. The accumulation of lutonarin and 3-feruloylquinic acid, but not of saponarin, was greatly enhanced by high PAR and further increased by UV exposure. Acclimation of plants to both high UV and PAR intensities also increased the total pool of xanthophyll-cycle pigments (VAZ). Subsequent exposure to HRS revealed that prior acclimation to UV and PAR was able to ameliorate the negative consequences of HRS on photosynthesis. Both total contents of epidermal flavonols and the total pool of VAZ were closely correlated with small reductions in light-saturated CO2 assimilation rate and maximum quantum yield of photosystem II photochemistry caused by HRS. Based on these results, we conclude that growth under high PAR can substantially increase the photoprotective capacity of barley plants compared with plants grown under low PAR. However, additional UV radiation is necessary to fully induce photoprotective mechanisms in the variety Barke. This study demonstrates that UV-exposure can lead to enhanced photoprotective capacity and can contribute to the induction of tolerance to high radiation stress in barley.
Keywords: Photosynthesis; Plant Leaves; fyziologický stres; Hordeum; tolerance záření; Dose-Response Relationship, Drug; Photoinhibition; ultrafialové záření; listy rostlin; Stress, Physiological; Photoprotection; Barley genotype; Polyphenols; ječmen (rod); vztah mezi dávkou a účinkem léčiva; Ultraviolet Rays; Radiation Tolerance; Xanthophylls; fotosyntéza